Atrazine and mancozeb induce excitotoxicity and cytotoxicity in primary cultures of mouse cerebellar cortex. Issue 8 (13th September 2016) - Peña-Contreras, Zulma; Miranda-Contreras, Leticia; Morales-Ovalles, Yasmin; Colmenares-Sulbarán, Melisa; Dávila-Vera, Delsy; Balza-Quintero, Alirio; Salmen, Siham; Mendoza-Briceño, Rosa Virginia
ABSTRACT: This work aimed to determine the neurotoxicity of atrazine and mancozeb by high performance liquid chromatography (HPLC) evaluation of neurotransmitters, and morphologically by flow cytometry and ultrastructural analysis using transmission electron microscopy of primary cultures of mouse cerebellar cortex. The latter revealed mitochondrial damage, synaptic alterations, and neuroinflammation, while neurochemical results showed augmented release of excitatory neurotransmitters with a consequent increase in excitation/inhibition ratio of atrazine- and mancozeb-treated cultures. This study shows that atrazine and mancozeb exposure may lead to neuronal damage associated with excitotoxicity and cytotoxicity.